Understanding adoption of the ecological and technological innovation of textile digital printing through Saudi enterprises - Baaqil, Khadijah Aidarous (My University, 2024)
The world is currently facing a climate crisis that cannot be resisted. Many businesses contribute to climate change by engaging in industrial activities and practices. For example, Saudi Arabia is the world’s largest exporter of total petroleum products, and its economy is heavily dependent on oil and petroleum-related industries (Odnoletkova & Patzek, 2021). These industries cause major environmental impacts in Saudi Arabia and surrounding areas. To move away from its oil dependency and implement sustainability, Saudi Arabia has heavily invested in other sectors, including the fashion industry (Rana & Suliman, 2018). However, the textile goods industry is considered the second most contaminated industry followed by the oil industry. One area of concern is the damage caused by dyeing and printing processes (Dhir, 2021). Technological innovations in the textile goods industry are creating solutions to reduce the negative impact of the industry (Sachs, 2019). Digital textile printing technology (DTP) is promoted as the future of sustainability in the fashion industry (Ayyoob & Khan, 2023; Kumelachew et al., 2023; Tkalec et al., 2022). However, there is limited information in the literature on digital textile printing (DTP) technology. Specifically, there are no studies investigating the factors influencing DTP adoption. Therefore, this study fills a gap in the literature by understanding the motivational and behavioral factors influencing DTP adoption in Saudi Arabia, through the lens of the modified Unified Theory of Acceptance and Use of Technology (UTAUT), considering performance expectancy, effort expectancy, facilitating conditions, social influence, eco-technological concern, and technological innovativeness. In order to achieve the objectives of this study, a mixed methods approach was employed through survey based primary data collection to gather both quantitative and qualitative data. Three models were proposed to investigate different relationships and variables to provide a comprehensive understanding of the research objectives and hypotheses. Model 1 used SEM-PLS for testing hypotheses and mediation relationships. Ordinal Logistic Regression (OLR) was used to test Model 2 and Model 3. Model 2 estimated the relationship between ordered categorical dependent variable and independents variables, and Model 3 estimated the influence of control variables in the adoption of DTP. The findings demonstrated that effort expectancy, social influence, and technological innovativeness have a significant influence on adoption. Conversely, there were three rejected hypotheses, including performance expectancy, facilitating conditions, and eco-technological concern, that showed a non-significant relationship with adoption. Additionally, the results highlighted that technological innovativeness strongly mediates between primary study variables and the adoption of DTP technology. Overall, the OLR result showed that all relationships between the study constructs are significant, and the model is robust. Analysis also revealed that DTP adopters were younger and have higher incomes. Yet, individuals with a higher education level had less likelihood of adoption. Furthermore, the qualitative findings confirmed some close-ended responses and added insights. Thematic analysis identified three benefits of DTP: innovation, production efficiency, and product results. Participants also reported challenges, such as a lack of skills, financial resources, and limited DTP suppliers. Study results revealed some positive implications for the DTP market. There are strategies that marketers and policymakers could implement to improve the rate of DTP adoption. For example, marketers should segment targeted market into groups based on their individual characteristics. Awareness of the environmental impact of the fashion industry should be increased to enhance sustainability in the Saudi market. Addressing the study factors holistically necessitates targeted interventions, such as awareness campaigns, training programs, and collaboration initiatives. Lastly, this study showed that the research model had the capability to explain the adoption of DTP technology.
Keywords: The Unified Theory of Acceptance and Use of Technology; Digital textile printing adoption; Eco-technology; Sustainable fashion business; Mixed methods research; Textile market